Vast potential for using the piggyBac transposon to engineer transgenic plants at specific genomic locations. Issue 1 (2nd January 2016) - Johnson, Eric T.; Owens, Jesse B.; Moisyadi, Stefan
ABSTRACT: The acceptance of bioengineered plants by some nations is hampered by a number of factors, including the random insertion of a transgene into the host genome. Emerging technologies, such as site-specific nucleases, are enabling plant scientists to promote recombination or mutations at specific plant loci. Off target activity of these nucleases may limit widespread use. Insertion of transgenes by transposases engineered with a specific DNA binding domain has been accomplished in a number of organisms, but not in plants. The piggyBac transposon system, originally isolated from an insect, has been utilized to transform a variety of organisms. The piggyBac transposase is amendable to structural modifications, and was able to insert a transgene at a specific human locus through fusion of a DNA binding domain to its N-terminus. Recent developments demonstrating the activity of piggyBac transposase in plants is an important first step toward the potential use of engineered versions of piggyBac transposase for site-specific transgene insertion in plants.